A Comparative Analysis of Pro-Japanese Imperialist Poetry in Malaysia and Korea, Seeking to Determine Korean Literature's Identity - Yong Soo, Kim (JOMANTARA, 2025)
When we looked back at history, we find various actions of nations that were about to be colonized in response to the colonization process by other nations. Those actions can be broadly divided into two categories: 'acceptance' and 'protest'. Meanwhile, the nature of acceptance and protest can be divided into two characteristics, namely progressive and passive. In Korea and Malaysia, which were once colonized by Japanese Imperialists in the past, we find acts of acceptance or protest in their history. We can evaluate the actions of someone who accepts various priorities from the colonizers in exchange for providing direct assistance and support to the colonizers, as progressive acceptance. Meanwhile, the process of adapting to the colonial system like fate can be said to be passive acceptance. Meanwhile, protests through physical force, including violence and the use of methods and means such as literature to inspire the struggle of the general public, can be considered progressive protests. Additionally, indirect protests can be classified as passive protests.